The Expulsion of the Jews and their Emigration to the Southern Low Countries (15th-16th C.) - Dequeker, Luc (Mediaevalia Lovaniensia - Series 1/Studia, 1998)
The present volume originates from a colloquium which was organized by the Belgian Institutum Judaicum and the Instituut voor Middeleeuwse Studies of the Katholieke Universiteit Leuven in a common effort to commemorate the tragical events in the history of European Jewry around 1492. The organisers intended to elucidate neglected aspects of the spiritual landscape of medieval Spain on the eve of the expulsion and to draw the attention, by way of a few examples, to the sequels of Jewish emigration for the intellectual circles in the Southern Low Countries during the 16th century.